An examination of the direct and interactive effects of race/ethnicity and gender on charge reduction. Issue 3 (27th May 2022) - Romain Dagenhardt, Danielle M.; Heideman, Amanda J.; Freiburger, Tina L.
ABSTRACT: Much of the prior literature on criminal court case processing has focused on judicial decisions regarding bail and sentencing. Fewer studies have examined prosecutorial decision-making, particularly charge reduction. Framed within the focal concerns perspective, this paper examined racial and gender disparity in charge reduction and whether disparity existed across different types of charge reduction. Findings demonstrated partial support for the focal concerns perspective with men and minority defendants less likely to receive a severity reduction.Implications for plea negotiation policies are discussed.